2017
DOI: 10.1186/s12906-016-1506-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of hepatoprotective agents against damage induced by acetaminophen and CCl4

Abstract: BackgroundIn vitro bioassays are important in the evaluation of plants with possible hepatoprotective effects. The aims of this study were to evaluate the pretreatment of HepG2 cells with hepatoprotective agents against the damage induced by carbon tetrachloride (CCl4) and paracetamol (APAP).MethodsAntioxidative activity was measured using an assay to measure 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging. The in vitro hepatotoxicity of CCl4 and APAP, and the cytotoxic and hepatoprotective proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…Therefore, this study was aimed to investigate the hepatoprotective effect of the constituents of D. villosa against H 2 O 2 -induced cytotoxicity and oxidative stress in HepG2 cell line. HepG2 cell line is well reported to be involved in the metabolism ( Kim et al, 2011 ) and have been proven to be a good model system for cytotoxicity assessment and cyto-protective potential of various compounds against the toxic substances ( González et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study was aimed to investigate the hepatoprotective effect of the constituents of D. villosa against H 2 O 2 -induced cytotoxicity and oxidative stress in HepG2 cell line. HepG2 cell line is well reported to be involved in the metabolism ( Kim et al, 2011 ) and have been proven to be a good model system for cytotoxicity assessment and cyto-protective potential of various compounds against the toxic substances ( González et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our studies demonstrated that ALT, AST and LDH activity could be variable in in vitro models. Enzyme activity in biofluids can be affected by the dose and duration of exposure to toxicants (González et al, ; Kia et al, ). Nevertheless, most miRNAs except for miR‐122 and miR‐193a were significantly elevated in the supernatants of HepG2 cell cultures consistent with cell viability (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, DON at 1 mg/kg elevated the ALT and GGT levels, suggesting that DON may destroy the liver cell membrane, leading toleakage of enzymes from injured hepatocytes [54,55]. However, compared with the 1 mg/kg DON group, DON at 3 mg/kg decreased serum levels of ALT, AST and LDH, especially AST and LDH, suggesting that 3 mg/kg DON may lead to massive necrosis of liver cells or acute hepatitis, basically resulting in depletion of transaminase in the liver tissue [56,57]. In addition, DON signi cantly increased the level of serum GLO, suggesting that DON may cause an in ammatory response and immune system disorders in piglet liver [58].…”
Section: Donmentioning
confidence: 96%